RELEVANSI DAN TANTANGAN PARAGMATISME DALAM MEMBENTUK PEMBELAJARAN YANG ADAPTIF - Guido Herlambang; Ahmad Ruslan (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
The relevance and challenges of pragmatisme in shaping adaptive leraning have become increasingly important ini modern educational settings. This study aims to explore the applicationof pragmatisme in education, particularly how it contributes to the development of adaptive leraning system. The recsearch was conducted throurh a qualitative approach, using literature review and analysis of existing educational practices in Indonesia. The findings suggest thet pragmatisme, with its emphasis on experiential learning and practical application of knowledge, play a crucial role in adapting education to the needs of the 21st century. It allows students to engage in real-world problem solving, fastering critical skills such as creativity, collaboration, and critical thinking. However, the study alsi identifie several challenges in implementing pragmatism, approaches, such as gaps between tehory and pratice, limited resources, and the rigidity of assessment systems. Despite these challengesn the research concludes that pragmatism provides significant potential for adaptive learning, with suggestions for improvements in teacher training, curriculum flexibility, and assessment reforms. Furter research is recommended to examine the impact of pragmatism on student outcomes acrodd various educational context and cultural settings.